Multi-switching compound-compound anti-synchronization of non-identical hyperchaotic systems. (4th March 2021) - Ibraheem, Aysha; Khan, Ayub
ABSTRACT: In this paper, a synchronization scheme for six non-identical hyperchaotic systems is investigated. The paper addresses a synchronization scheme of five leader (master) and one follower (slave) non-identical hyperchaotic systems. This synchronization scheme is first of its kind and different from existing schemes as instead of a scaling system a compound scaling signal is used. The presented scheme is termed as 'multi-switching compound-compound anti-synchronization' (MCCAS). Asymptotically stable synchronized states are established between leader and follower systems by employing nonlinear control method and Lyapunov stability criteria. Additional leader systems and hyperchaotic systems enhance the complexity of this synchronization scheme which is useful in secure communication. The information signal can be split and loaded with different signals of leader systems to increase the grade of security. To justify the theoretical results, an example is considered where Pang-Liu, Zheng, Chen, Liu and Newton-Leipnik hyperchaotic systems are considered as leader systems and Lorenz hyperchaotic system is considered as a follower system. Theoretical results are confirmed by graphical analysis.